Prevalence and clinical outcomes of dystrophin‐associated dilated cardiomyopathy without severe skeletal myopathy. (9th June 2021) - Restrepo‐Cordoba, Maria A.; Wahbi, Karim; Florian, Anca R.; Jiménez‐Jáimez, Juan; Politano, Luisa; Arad, Michael; Climent‐Paya, Vicente; Garcia‐Alvarez, Ana; Hansen, Rasmus B.; Larrañaga‐Moreira, José M.; Kubanek, Milos; Lopes, Luis R.; et al.
Abstract: Aims: Dilated cardiomyopathy (DCM) associated with dystrophin gene ( DMD ) mutations in individuals with mild or absent skeletal myopathy is often indistinguishable from other DCM forms. We sought to describe the phenotype and prognosis of DMD associated DCM in DMD mutation carriers without severe skeletal myopathy. Methods and results: At 26 European centres, we retrospectively collected clinical characteristics and outcomes of 223 DMD mutation carriers (83% male, 33 ± 15 years). A total of 112 individuals (52%) had DCM at first evaluation [ n = 85; left ventricular ejection fraction (LVEF) 34 ± 11.2%] or developed DCM ( n = 27; LVEF 41.3 ± 7.5%) after a median follow‐up of 96 months (interquartile range 5–311 months). DCM penetrance was 45% in carriers older than 40 years. DCM appeared earlier in males and was independent of the type of mutation, presence of skeletal myopathy, or elevated serum creatine kinase levels. Major adverse cardiac events (MACE) occurred in 22% individuals with DCM, 18% developed end‐stage heart failure and 9% sudden cardiac death or equivalent. Skeletal myopathy was not associated with survival free of MACE in patients with DCM. Decreased LVEF and increased left ventricular end‐diastolic diameter at baseline were associated with MACE. Individuals without DCM had favourable prognosis without MACE or death during follow‐up. Conclusions: DMD ‐associated DCM without severe skeletal myopathy is characterized by incomplete penetrance but high risk of MACE, including progression to end‐stage heart failure and ventricular arrhythmias. DCM onset is the major determinant of prognosis with similar survival regardless of the presence of skeletal myopathy. Abstract : Main characteristics of DMD ‐associated dilated cardiomyopathy (DCM). DMD ‐associated DCM shows incomplete penetrance and a later diagnosis among DCM patients without concomitant skeletal myopathy. DMD mutations result in progressive cardiomyocyte death and fibrosis, leading to DCM. DCM onset is the major determinant of prognosis. Prognosis is similar among DMD ‐associated DCM patients with or without skeletal muscle involvement. DMD, dystrophin gene; HF, heart failure; HT, heart transplantation; ICD, implantable cardioverter‐defibrillator; LVAD, left ventricular assist device; SCD, sudden cardiac death.